Policy Parity for CCS? – Public Preference on Low Carbon Electricity. (July 2017) - Itaoka, Kenshi; Saito, Aya; Akai, Makoto
Abstract: To examine the rationale for policy parity of three basic low carbon power sources, the consumer preference for those power sources was evaluated by choice experiment through a public survey in December 2015 - January 2016. A sample with decent representativeness was obtained by two stage stratified sampling and door-to-door canvassing. The choice questions were designed with realistic attributes simulating power retail market starting from April 2016. Through the data analysis, using random parameter logit model, we found that respondents' WTP shows that they considered not only CO2 emission reductions but also the characteristics of the three methods of low carbon power generation. It is also found that WTP is 11 yen per 1% increase in renewables, 14 yen per 1% decrease in nuclear (this WTP varies from one individual to another), and 4 yen per 1% increase in thermal power generation with CCS. The results of WTPs for the share of renewables and CCS in the power mix of new electricity retail companies in the future market rationalizes the necessity of policy parity to some extent for those technologies implying inclusion of CCS in the FIT but not nuclear.